PENERAPAN METODE COURSE REVIEW HORAY UNTUK MENINGKATKAN KETERAMPILAN BERKOLABORASI DAN BERFIKIR KRITIS - Novia Rahma Dina; Ahna Hailu Shabilah (Kajian Moral dan Kewarganegaraan, 2026)
The Course Review Horay (CRH) method is an active learning approach that emphasizes student engagement through effective collaboration and communication. This research aims to examine the implementation of the CRH method in enhancing collaboration and critical thinking skills among students at MI Al-Hidayah. A quantitative approach with an experimental design was employed in this study. The findings indicate that the application of the CRH method significantly improved students' collaboration and critical thinking skills. This improvement was observed through tests, observations, and interviews conducted during the study. The method provided opportunities for students to actively interact in group discussions, which stimulated critical thinking and teamwork skills. Therefore, the CRH method is an effective alternative to improve the quality of learning at MI Al-Hidayah. Keywords: Course Review Horay, collaboration skills, critical thinking, learning method, MI Al-Hidayah.